Nearshore circulation revealed by wastewater discharge from a submarine outfall, Aveiro Coast, Portugal - Silva, J. F. (2015)
The morphological and climatic conditions of the Atlantic coast of northern Portugal result in a prevailing upwelling circulation over the continental shelf. A submarine outfall releases wastewater into the ocean c. 3 km directly offshore (at ~16 m water depth) from S. Jacinto, 5 km to the north of the inlet to the estuarine coastal lagoon system of the Ria de Aveiro. The buoyant plume has a distinctive reddish brown colour and is clearly visible at the water surface. The transport and dispersion of the plume was monitored by airborne photography and by in situ water sampling. Results revealed the surface currents present and water mass fronts in the nearshore zone of the Aveiro coast. During the spring and summer, the plume was not transported offshore in the manner expected by the upwelling shelf circulation. Instead, it was commonly observed to be transported alongshore with the prevailing southerly circulation or with an onshore component. The transport to the south caused the outfall plume to interact with the circulation associated with the tidal currents generated in the inlet channel to the Ria de Aveiro. The observations suggest that the trophic status of the Ria de Aveiro is unlikely to change because of the operation of the submarine outfall. Furthermore, this study demonstrates how simple observations of wastewater discharge from a submarine outfall can be used to improve understanding of nearshore circulation.